Thioureas as Ligands in Organometallic Reactions - Li, Jingjie; Shi, Li-Li; Chen, Jiahua; Gong, Jianxian; Yang, Zhen (Synthesis, 2014)
Thioureas are air and moisture stable, and they can coordinate to various metal centers, making their derivatives versatile ligands for transition-metal-catalyzed reactions. This account provides an overview of recent developments in the use of thioureas as ligands in organometallic-catalyzed reactions, with particular emphasis on their application to the total synthesis of natural products.1 Introduction2 Development of Thioureas as Ligands in Transition-Metal-Catalyzed Reactions2.1 Carbonylative Annulation2.2 Pauson–Khand Reaction (Intramolecular and Intermolecular)2.3 Thiourea–Palladium-Catalyzed Carbonylation of Terminal Olefins2.4 Thiourea–Palladium-Catalyzed Heck Coupling Reaction2.5 Suzuki Coupling and Suzuki Carbonylative Reaction2.6 Negishi Coupling2.7 Other Reactions3 Applications in Total Synthesis of Natural Products3.1 (±)-Schindilactone A3.2 Crisamicin A4 Conclusion and Outlook
Keywords: thiourea; carbonylative annulation; transition metal; cobalt; palladium